Assessment of Mangrove Species Diversity in the Municipality of Nasipit, Agusan del Norte, Philippines - Pulido, Rhea Lou; Casendac, Elena Fe; Rozano, Michael Jeff; Jandug, Catherine Mhae; Obo, Liezel; Sabado, Jessa Marie; Elvira, Marlon; Corbita, Victor (Jurnal Sylva Lestari, 2025)
Mangrove habitats are the most productive and biologically diverse ecosystems in the world. This study assessed the community structure of mangrove species in the two villages of Nasipit, Agusan del Norte, Philippines. There were 10 sampling quadrats with a size of 20 m × 20 m in Barangay (Village) Ata-atahon and Camagong. The data collected include taxonomic names, species diversity, and vegetation analysis. The results of the study revealed that Ata-atahon and Camagong fell under low diversity, as indicated by their Shannon-Wiener Index values of 1.091 and 0.873, respectively. The evenness index showed that Camagong has high evenness compared to Ata-atahon. Moreover, all species found in the two areas were listed as least concern based on the IUCN Red List for its conservation status. Both barangays being studied located at Nasipit, Agusan del Norte, fell under the low category due to anthropogenic activities. These results suggest the need for the rehabilitation and enrichment of the mangrove forest in Nasipit, Agusan del Norte, which could be led by the Department of Environment and Natural Resources in collaboration with the local government and non-governmental organizations. It is also strongly recommended to adopt preventive measures to prevent habitat loss. Keywords: anthropogenic, conservation, dominance, species diversity, species importance value